Clinical Relevance of Faecal Calprotectin Level in Infantile Colic: A Cross-sectional Survey - Iraj Shahramian; Ali Bazi; Alireza Sargazi; Omolbanin Sargazi Aval; Alireza Dechal; Mostafa Bazzi; Masoud Jahantigh (Mashhad University of Medical Sciences, 2018)
Background: There is limited knowledge on the potential applicability of fecal calprotectin (f-CP) as an inflammatory screening parameter in infantile colic (IC). This study aimed to evaluate f-CP in neonates with IC as a useful diagnostic indicator regarding this condition. Methods: The present study was conducted on 100 cases, including 50 newborns with IC and 50 non-colicky neonates. The diagnosis of IC was fulfilled by the Wessel Criteria. The level of f-CP was determined by a specific enzyme-linked immunosorbent assay kit (Calprotectin ELISA, EuroImmun, Germany). The statistical analysis was performed in SPSS software (version 19).   Results: Out of 100 neonates, 57 cases were male and 43 subjects were female. The age spectrum ranged from 19-90 days (40.4±15.9). Colicky newborns were slightly younger (P=0.06) with higher birth weight compared to the infants without colic (P